2020
DOI: 10.3390/agronomy10101554
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Canopy Size, Light Penetration and Photosynthesis of Three Cassava Genotypes with Different Canopy Architectures

Abstract: The objective of this study was to investigate the effect of canopy size (CS) on light penetration and leaf photosynthesis of three cassava genotypes (Kasetsart 50 (KU50), Rayong 11 and CMR38-125-77) under two planting dates in two years. Data were recorded for CS, leaf area index (LAI), leaf photosynthesis, biomass (BM), storage root yield (SRY), starch content (SC) and harvest index (HI). The variation of CS depended on temperature, solar radiation (SR), relative humidity (RH) and day length (DL). In early g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…For cassava planted in June (Rainy PD) and December (Cool PD2), at 3MAP, CMR38-125-77 had the highest LAI (Table 1), which corresponded to its lowest percent light penetration (Figure 3), and therefore high light interception by leaves at the upper canopy levels. Similar findings were reported for cassava planted in May 2016 (rainy season) and November 2015 (cool season), LAI of the 3MAP plants were higher in CMR38-125-77 than Rayong 11 and Kasetsart 50 [30]. Moreover, for the Rainy PD, CMR38-125-77 recorded the highest Pn at five canopy levels, and for the Cool PD2, it showed the highest Pn at three canopy levels, resulting in the highest mean Pn (Table S2).…”
Section: Genotype Variation In Canopy Structure and Photosynthesissupporting
confidence: 84%
See 4 more Smart Citations
“…For cassava planted in June (Rainy PD) and December (Cool PD2), at 3MAP, CMR38-125-77 had the highest LAI (Table 1), which corresponded to its lowest percent light penetration (Figure 3), and therefore high light interception by leaves at the upper canopy levels. Similar findings were reported for cassava planted in May 2016 (rainy season) and November 2015 (cool season), LAI of the 3MAP plants were higher in CMR38-125-77 than Rayong 11 and Kasetsart 50 [30]. Moreover, for the Rainy PD, CMR38-125-77 recorded the highest Pn at five canopy levels, and for the Cool PD2, it showed the highest Pn at three canopy levels, resulting in the highest mean Pn (Table S2).…”
Section: Genotype Variation In Canopy Structure and Photosynthesissupporting
confidence: 84%
“…Earlier work reported that from 4MAP to 5MAP, cassava generally attained an LAI of around 3.0 when the plants received 90% light interception [79] and the plants should reach the maximum LAI of 3.0-3.5 m 2 m −2 as quickly as possible to obtain optimum yield [12,27]. However, more recent research using improved high-yielding cultivars growing in well-watered fields in tropical savanna climate reported higher LAI values between 4.0 to 5.0 m 2 m −2 at 5MAP to 6MAP [30,80]. In this study, the canopy structures of cassava plants at 6MAP planted in different seasons showed more variation than those observed at 3MAP (Table 1).…”
Section: Canopy Structure and Photosynthesis Of Cassava Plants At 6mapmentioning
confidence: 99%
See 3 more Smart Citations